CeAF Ameliorates Diabetic Wound Healing by Alleviating Inflammation and Oxidative Stress via TLR4/NF-κB and Nrf2 Pathways. (5th April 2023) - Li, Shiyan; Ding, Xiaofeng; Yan, Xin; Qian, Jin; Tan, Qian
Abstract : Background . With the rise in diabetes incidence, diabetic foot ulcers have become the most common clinically chronic refractory wounds. Persistent chronic inflammation is a typical feature of diabetic cutaneous wounds, and diabetic wound healing can be improved by alleviating inflammation and oxidative stress. Chick early amniotic fluids (ceAF) consist of native conglutinant substances with balanced amounts of growth factors, cytokines, and chemokines. However, whether ceAF modulates inflammation and oxidative stress and thus promotes diabetic wound healing remains unknown. Materials and Methods . RAW264.7 cells were categorized into four groups: negative control, LPS, LPS + ceAF, and ceAF. 10% of ceAF was selected to treat different groups of mice with a full-thickness skin defect wound. Then, RT-qPCR, western blot, immunofluorescence, and other assays were carried out to explore the effect of ceAF on wound healing and its molecular mechanism. Results . Topical administration of ceAF improved M2 macrophage polarization and inflammatory response in the wound tissues, thereby ameliorating delayed wound healing. Histological improvement could be observed in the grade of inflammation, collagen deposition, and neovascularization in wound edge tissues. ceAF also increased M2 macrophage-specific markers expression and exogenous ceAF suppressed LPS-induced cellular inflammatory response in vitro high glucose environment. Additionally, ceAF could activate TLR4/NF- κ B and Nrf2 signal transductions to promote M2 macrophage polarization in vitro . Conclusions . In summary, ceAF downregulates inflammatory response, regulates M2 macrophage transition via TLR4/NF- κ B and Nrf2 signaling pathways, and thus improves diabetic wound healing.